PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI MINI MARKET FAJRI MART KECAMATAN TAMPAN KOTA PEKANBARU - Faiz Rizaqy Hardewo; Gimin Gimin; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This study aims to determine the effect of service quality and price on purchasing decisions in Fajri Mart Mini Market, Tampan District, Pekanbaru. The population of this study is all consumers of Mini Market Fajri Mart, with a sample of 140 consumers. The method used is interviews and sampling techniques using accidental sampling. Data analysis used is multiple linear regression. The results showed that service quality and price had an effect on purchasing decisions. This can be seen from the multiple linear regression equation Y = 5.172 + 0.176X1 + 0.289X2. Judging from the calculation of R2 (R Square) service quality and price affect the purchasing decision amounting to 56.2% while the remaining 43.8% is influenced by location, promotion and discount. Key Words: service qulity, price, purchasing decisions